2012
DOI: 10.1021/jp305352b
|View full text |Cite
|
Sign up to set email alerts
|

Prototropic Interactions of Pyrimidine Nucleic Acid Bases with Acridine: A Spectroscopic Investigation

Abstract: In this article, we have investigated the interactions of three pyrimidine nucleic acid bases, cytosine (C), thymine (T), and uracil (U) with acridine (Acr), an N-heterocyclic DNA intercalator, through the changes in photophysics of Acr inside SDS micelles. Fluorescence of AcrH(+)* at 478 nm and its lifetime are quenched on addition of C, T, and U, while a concomitant increment of Acr* is observed only with C. However, the relative amplitude of Acr* increases with a simultaneous decrease in AcrH(+)* only with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…This is probably due to the solubilization of the organic molecule in the hydrophobic portion of the micelle bringing close contact between the substrate and borohydride. The confinement effect often results in uncommon photophysics and charge transfer phenomena. Recently, we have found that the electrostatic interactions between the micelle and CDs influence their ET ability . We anticipate similar effects to be operating here with the highly negatively charged surface of the anionic RCDs interacting strongly with the cationic CTAB micellar surface by electrostatic attraction.…”
Section: Results and Discussionmentioning
confidence: 67%
“…This is probably due to the solubilization of the organic molecule in the hydrophobic portion of the micelle bringing close contact between the substrate and borohydride. The confinement effect often results in uncommon photophysics and charge transfer phenomena. Recently, we have found that the electrostatic interactions between the micelle and CDs influence their ET ability . We anticipate similar effects to be operating here with the highly negatively charged surface of the anionic RCDs interacting strongly with the cationic CTAB micellar surface by electrostatic attraction.…”
Section: Results and Discussionmentioning
confidence: 67%
“…Time-resolved emission spectra are detected by using a picosecond pulsed diode laser-based TCSPC spectrometer and MCP-PMT as a detector [43][44][45] . The emission from the sample is collected at a right angle to the direction of the excitation beam, maintaining the magic angle polarization with a bandpass of 4 nm.…”
Section: (C) Time-correlated Single-photon Counting (Tcspc)mentioning
confidence: 99%
“…A concomitant decrease in the lifetime of 1.81 μs for U CDs at 360 nm (peak-I, triplet π-π*) is observed, while the lifetimes for O CDs and R CDs are enhanced to 2.25 and 2.18 μs respectively. This is a clear indication of alteration of the dynamics of the multiple excited transition states for the >C=C< and >C=O bonds, and the isosbestic point at 375 nm establishes the equilibrium between the two forms in the triplet states, due to keto-enol tautomerism in the CDs upon surface modification 45,49,[54][55][56] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 Scheme-1: The proposed mechanism between singlet and triplet inter system crossing based on possible allowed transitions.…”
Section: (F) Atomic Force Microscope (Afm)mentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The use of the compounds in this role emerges from their ability to occur in the electronically excited state in various structural forms (tautomeric, rotameric, protolytic) each of which have different fluorescent features (emission wavelengths, lifetimes) which depend on the properties of the medium (such as polarity, acidity/basicity, hydrogenbonding ability) or biological environment. One group of compounds that are widely used as ESPT fluorophores are hydroxyflavones (hydroxy-2-phenyl-4H-chromen-4-ones), 12 …”
Section: Introductionmentioning
confidence: 99%